RMD86, a thiophene derivative, promotes antinociceptive and antipyretic activities in mice. Issue 11 (November 2020) - da Cruz, Ryldene Marques Duarte; Braga, Renan Marinho; de Andrade, Humberto Hugo Nunes; Monteiro, Álefe Brito; Luna, Isadora Silva; da Cruz, Rayssa Marques Duarte; Scotti, Marcus Tullius; Mendonça-Junior, Francisco Jaime Bezerra; de Almeida, Reinaldo Nóbrega
Abstract: Treatment of pain and fever remains an important challenge for modern medicine. Non-steroidal anti-inflammatory drugs (NSAIDs) are the pharmacological options most often used, but their frequent use exposes the patient to serious side effects and dangerous drug interactions. In this context, thiophene derivatives are promising therapeutic alternatives. In this study, we evaluated the in vivo and in silico antinociceptive and antipyretic properties of RMD86, a thiophene derivative. At 100 mg/kg, RMD86 induced no significant changes in the motor coordination of mice in the Rotarod test. At 25, 50, and 100 mg/kg RMD86 significantly reduced the number of abdominal contortions induced by acetic acid (antinociceptive activity) in mice when compared to the control. In the formalin test, for the first phase, there was a reduction in licking times at doses of 50 and 100 mg/kg. In the second phase, reduction occurred at all doses. In the hot plate test, RMD86 (at 100 mg/kg) increased latency time in the first 30 min. For antipyretic activity, RMD86, when compared to the reference drug acetaminophen (250 mg/kg), significantly reduced pyrexia at 30, 60, and 120 min, at dosages of 25, 50 and 100 mg/kg. Molecular docking studies revealed that RMD86 presents a greater number of interactions and lower energy values than both the co-crystallized ligand and the reference drug (meloxicam) against COX-1 and COX-2 isoenzymes. The results give evidence of the analgesic and antipyretic properties like NSAIDs suggesting its potential for pain therapy. Abstract : Antipyretic activity; Antinociceptive activity; 2-amino-thiophene derivative; Molecular docking; Biological sciences; Neuroscience; Behavioral neuroscience; Behavioral test; Nervous system.